Bimbingan dan Konseling Sekolah di Era Society 5.0: Sebuah Kajian Sistematis - Prayoga, Ammi; Purwoko, Budi; Habsy, Bakhrudin All (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
Entering the era of society 5.0 where the integration between technology and humans is very close. This will also have an impact on the process of providing guidance and counseling services in the school environment. Guidance and counseling in the era of society 5.0 must be able to adapt to very rapid social developments and changes. Student problems are currently increasingly complex and require guidance and counseling services to be provided, however, the condition of guidance and counseling teachers whose time is limited and the number of teachers is less than proportional is a challenge in itself. Information technology is one alternative that can be used to answer these challenges. Many innovations in the field of guidance and counseling by utilizing information technology have been carried out by BK academics. This journal uses a systematic literature review method in an effort to summarize the innovation of guidance and counseling services in utilizing information technology which is included in the professional competence of guidance and counseling teachers. Guidance and guidance teachers at schools often use social media and the internet. In this regard, it can be used to optimize guidance and counseling services at schools in the era of society 5.0. _____________________________________________________________Memasuki era society 5.0 dimana integrasi antara teknologi dan manusia sangat erat. Hal ini juga akan berdampak pada proses pemberian layanan bimbingan dan konseling di lingkungan persekolahan. Bimbingan dan konseling pada era sociey 5.0 harus dapat beradaptasi dengan perkembangan dan perubahan sosial yang sangat cepat. Permasalahan siswa pada saat ini semakin komplek dan medesak untuk diberikan layanan BK, namun kondisi Guru BK yang waktunya terbatas dan jumlah guru yang kurang porposional menjadi tantangan tersendiri. Teknologi informasi menjadi salah satu alternatif yang bisa dilakukan untuk menjawab tantangan tersebut. Inovasi dalam bidang bimbingan dan konseling dengan memanfaatkan teknologi informasi sudah banyak dilakukan oleh para akademisi BK. Jurnal ini menggunakan metode systematic literature review dalam upaya merangkuman inovasi layanan BK dalam memanfaatkan teknologi informasi yang tercakup pada kompetensi profesional Guru BK. Guru BK disekolah sudah sering menggunakan sosial media dan internet. Berkaitan dengan hal tersebut dapat dimanfaatkan untuk mengoptimalkan layanan BK disekolah pada era society 5.0.